Antimicrobial Sensitivity Pattern of Salmonella spp. Clinical Isolates in Blood Culture: A Tertiary Center Study - Gani, ABM Shakil; Wadud, Ayman; Rahman, Mizanur; Roy, Sushmita; Aktari, Selin (Journal of Shaheed Suhrawardy Medical College, 2020)
Objective: Bangladesh is an endemic area for enteric fever. Adequate and timely antimicrobial treatment invariably cures this disease. But resistant strains of Salmonella spp. have made it difficult to treat nowadays. This study will help clinicians in understanding the local resistance pattern of enteric fever and identifying recent changes in the trends of the sensitivity pattern of commonly used antibiotics in Bangladesh. Materials and Methods: This cross-sectional study was conducted during the period from January 2016 to June 2019 in Sheikh Hasina Medical College, Tangail, to determine the antimicrobial sensitivity patterns of Salmonella typhi and paratyphi isolated by blood culture from clinically suspected typhoid fever patients. The blood sample was processed on BACTEC 9050 and isolates obtained from subculture were serotyped. Then antibiotic susceptibility testing was carried out using the disk diffusion method. Results and Discussion: A total of 137 cases were recorded in four years. All cephalosporins were found sensitive in more than 90% of cases. We did not find any resistance to Ceftriaxone in our patients’ group. Moxifloxacin and Levofloxacin showed higher sensitivity than Ciprofloxacin (100% and 96% Vs 90%). Nalidixic acid demonstrated lower sensitivity than previously reported (less than 5%), while Gentamicin showed the highest sensitivity around 100%. Conclusion: Multidrug-resistant (MDR) Salmonella typhi and paratyphi are emerging rapidly. To overcome this global issue, rational use of antibiotics has to be ensured. Physicians should also be aware of the local resistance pattern so that they can treat their patients effectively. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 134-137